Talking about sex in Malawi: toward a better understanding of interpersonal communication for HIV prevention - Rupali J. Limaye; Rajiv N. Rimal; Glory Mkandawire; Peter Roberts; William Dothi; Jane Brown (SAGE Publishing, 2012)
The generalised AIDS epidemic in Malawi presents many challenges. As communication and advice from parents, peers, and partners are important factors in influencing sexual behaviour, understanding communication may provide insights into behaviour change programming. This mixed-method study used a household survey (n=1812) and 15 focus group discussions from the southern districts of Malawi to explore communication about sex and sexuality. Quantitative study findings point to the idea that self-efficacy, perceived benefits, and injunctive norms about talking about condom use are important factors influencing intentions to discuss condom use with partners. Qualitative study findings found that communication regarding sex between parents and children, partners, and peers was not common, and when there was communication, messages about sex focused on negative consequences of sexual activity. In Malawi, there is a need to increase efficacy in talking about sex and protective sexual behaviours, including condom use. Interventions should include components to increase communication skills, shift norms about sexual communication, and provide alternative mechanisms for individuals to gather pertinent information regarding their sexual behaviour.